Social Networks and the Labour Market Mismatch - Eleni Kalfa; Matloob Piracha (Institute for the Study of Labor (IZA), 2015)
This paper assesses the extent to which social contacts and ethnic concentration affect the education-occupation mismatch of natives and immigrants. Using Australian panel data and employing a dynamic random effects probit model, we show that social capital exacerbates the incidence of over-education, particularly for females. Furthermore, for the foreign-born, ethnic concentration significantly increases the incidence of over-education. Using an alternative index, we also show that social participation, friends and support and ethnic concentration are the main contributors in generating a mismatch, while reciprocity and trust does not seem to have any effect on over-education for both, immigrants and natives. Finally, we show that social networks are more beneficial for the relatively better educated.
Keywords: F22; J61; Z13; 330; social capital; ethnic concentration; over-education